1991
DOI: 10.12938/bifidus1982.10.2_123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yogurt and Yogurt Supplemented with Bifidobacterium and/or Lactulose in Healthy Persons: A Comparative Study

Abstract: Three types of yogurt supplemented with Bifidobacterium alone, lactulose alone, or both Bifidobacterium and lactulose were fed to healthy persons, who were tested before and after administration. Plain yogurt was fed during a control period. Yogurt containing both Bifidobacterium and lactulose resulted in greater improvement in the form and frequency of feces than the other yogurts. No differences were noted in blood chemistry test results before and after the administration of each type of yogurt. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…1998; De Preter et al. 2004, 2007, 2008), and similar results have been reported with other probiotics (Goldin & Gorbach 1976; Tomoda et al. 1991; Brigidi et al.…”
Section: Probiotic Potential For Older Peoplesupporting
confidence: 87%
“…1998; De Preter et al. 2004, 2007, 2008), and similar results have been reported with other probiotics (Goldin & Gorbach 1976; Tomoda et al. 1991; Brigidi et al.…”
Section: Probiotic Potential For Older Peoplesupporting
confidence: 87%
“…The increase in fecal bifidobacteria after lactulose ingestion has been reported in various studies using culture-based methodologies (1,3,31,39,40) and fluorescent in situ hybridization analysis (41). To our knowledge, this is the first human study using DGGE and RT-PCR in an integrated approach to indicate an in vivo bifidogenic effect of lactulose.…”
Section: Discussionmentioning
confidence: 64%
“…However, relatively few studies have been performed in this field and the results have been conflicting. Some studies noted an increase in defecation frequency [8][9][10] or a reduction in the need for laxatives [11], while in other studies no improvement could be observed [12][13][14][15]. Because of these conflicting results it remains unclear whether probiotics can relieve constipation.…”
Section: Discussionmentioning
confidence: 99%